Family Limitation - Sanger, Margaret, 1879-1966 (London : Bakunin Press, 1920)
1920 1920 1920s 16 pages : illustrations 6 FAMILY LIMITATION a man of the strongest will-power to be certain that he has withdrawn before any of the semen has been deposited in the vagina. It is very difficult to determine exactly whether this has been done. The greatest objection to this is the evil effect upon the woman's nervous condition. If she has not completed her desire, she is under a highly nervous tension, her whole being is perhaps on the verge of satisfaction. She is then left in this dissatisfied state. This does her injury. A mutual and satisfied sexual act is of great benefit to the average woman, the magnetism of it is health giving. When it is not desired on the part of the woman and she has no response, it should not take place. This is an act of prostitution and is degrading to the woman's finer sensibility, all the marriage certificates on earth to the contrary notwithstanding. Withdrawal on the part of the man should be substituted by some other means that does not injure the woman. DOUCHE A CLEANSER — NOT A PREVENTIVE. Although an antiseptic douche is an important factor in preventing conception, it should not be relied upon as a preventive measure in itself. A douche is a cleanser, but it is not of itself to be advised as a reliable method to prevent conception. When one understands how conception takes place, it can be seen at once that it is quite possible for a woman to be in a state of pregnancy before she leaves the bed, or before she can reach a douche, unless the womb has been previously covered with the rubber pessary, or by the ingredients of a suppository. Nevertheless, every woman should learn to cleanse herself thoroughly, by means of the vaginal douche. Some women object to the use of the suppository because of its lubricant effect ; this can be modified greatly by the use of a warm salt douche, taken just previously to inserting the suppository, cleansing the parts thoroughly of any secretions already there. Cold water douches are not advised, as there is a tendency to chill and shock the nervous system. A warm or moderate douche is advised. The use of warm soapsuds as a douche is used by women in France in the rural districts ; just plain, common soap, as a cleansing douche after the act. 15X/2/490/4